2001
DOI: 10.1007/s11661-001-0114-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase equilibria investigations on the aluminum-rich part of the binary system Ti-Al

Abstract: The binary system Ti-Al has been reinvestigated in the composition range of 50 to 76 at. pct Al by X-ray diffraction, metallography, electron probe microanalysis (EPMA), and differential thermal analysis (DTA). Heat-treated alloys (600 ЊC to 1300 ЊC) as well as the as-cast alloys were investigated. Seven stable intermetallic phases were observed: TiAl, Ti 1Ϫx Al 1+x , Ti 3 Al 5 , TiAl 2 , Ti 5 Al 11 , TiAl 3 (h), and TiAl 3 (l); two metastable phases, TiAl 2 (m) and TiAl 3 (m), were also found. For each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(37 citation statements)
references
References 22 publications
(11 reference statements)
6
31
0
Order By: Relevance
“…The pattern indicates that TiAl 20) and Ti 1ÀX Al 1þX 25) exist. This result agrees well with the detailed Ti-Al binary phase diagram presented by Braun and Ellner, 21) indicating that the high-temperature phases are successfully maintained by quenching. Ti-65.5 at%Al corresponds to the composition of the TiAl 2 layer formed at 1573 K and to that of the matrix region of TiAl 2 formed at 1673 K. Figure 5(b) shows the pattern for Ti-65.5 at%Al quenched from 1673 K. Ti 1ÀX Al 1þX and a small amount of hTiAl 2 26) are detected in the pattern.…”
Section: Phase Sequence At the Bonding Temperaturessupporting
confidence: 91%
See 2 more Smart Citations
“…The pattern indicates that TiAl 20) and Ti 1ÀX Al 1þX 25) exist. This result agrees well with the detailed Ti-Al binary phase diagram presented by Braun and Ellner, 21) indicating that the high-temperature phases are successfully maintained by quenching. Ti-65.5 at%Al corresponds to the composition of the TiAl 2 layer formed at 1573 K and to that of the matrix region of TiAl 2 formed at 1673 K. Figure 5(b) shows the pattern for Ti-65.5 at%Al quenched from 1673 K. Ti 1ÀX Al 1þX and a small amount of hTiAl 2 26) are detected in the pattern.…”
Section: Phase Sequence At the Bonding Temperaturessupporting
confidence: 91%
“…[21][22][23][24] Then, the influence of the cooling rate on the formation process of the interfacial microstructures was investigated at first. Figure 4 shows the influence of the cooling rate on the interfacial microstructure of the SiC/TiAl joints bonded at 1573 K for 32.4 ks.…”
Section: Phase Sequence At the Bonding Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] ), which indicates that the chemical composition of the titanium trialuminide deviates from the stoichiometric composition of Al 3 Ti. Local EDX chemical analyses performed on large grains of this intermetallic phase in longtime heat-treated sample (24 h at 750 C) revealed that Al 3 Ti was doped with Si, which replaces aluminum in the crystal structure of Al 3 Ti.…”
Section: Interface Reactions In the System Alsi7mg06/tiomentioning
confidence: 99%
“…With melting point of 1463°C, γ -TiAl (L1 0 -type) has a wide solubility range from the near stoichiometry to the Al-rich side (Braun and Ellner 2001;Nakano et al 1999). In the near stoichiometric Ti-rich side, alloys mostly consist of two phases, γ -TiAl and α 2 -Ti 3 Al.…”
Section: Reviewmentioning
confidence: 99%